ANALISIS KINERJA KEUANGAN PT ASTRA OTOPARTS TBK PERIODE 2014–2023 BERDASARKAN RASIO LIKUIDITAS, SOLVABILITAS, DAN PROFITABILITAS - Mustafida, Hidayatul; Puji Muniarty (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study aims to analyze the financial performance of PT Astra Otoparts Tbk during the period 2014–2023 using financial ratio analysis, including liquidity, solvency, and profitability ratios. This research employs a descriptive method with a quantitative approach. The data used in this study are secondary data obtained from the company’s annual financial reports published officially.The results indicate that the company’s liquidity ratio is generally in good condition, although it experienced a decline in 2020 due to the impact of the COVID-19 pandemic. The solvency ratio shows a relatively stable trend, with an increase in debt ratio during the pandemic period, followed by improvement in the subsequent years. Meanwhile, profitability ratios tend to fluctuate, with a significant decrease in 2020 and gradual recovery during 2021–2023.These findings suggest that PT Astra Otoparts Tbk has the ability to maintain its financial stability despite external economic pressures. The company demonstrates resilience by improving its financial performance after experiencing a downturn during the pandemic. This study contributes to financial management literature by providing a comprehensive analysis over a long-term period, including pre-pandemic, pandemic, and post-pandemic conditions.